Transformative Planungskapazitäten im transformativen Wandel der Mobilitätssysteme - Grundel, Ida; Trygg, Kristina (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
There is increasing urgency to tackle the ongoing climate crisis. New innovations, policies, tools and changes in habits related to our transport systems, especially the need to decrease people’s car dependency, are necessary. Recently, the redesign of city planning through urban experimentation to reduce car dependency has become a common planning tool in many cities. This paper addresses how Swedish municipalities are implementing innovations in transport and mobility through urban experimentation and their work with mobility hubs. Importantly, we wanted to understand the ways in which the municipalities are working with urban experiments towards transformative change and how local authorities are increasingly applying experimental governance approaches. Our empirical material builds on interviews and workshops with local officials and planners, and an analysis of policy documents in the municipalities. Our results show that the influence of local conditions and the planning environment matters for how transformative planning is practised. Communication around future visions and goals is an important aspect of implementing new tools for change. The implementation of new innovations in the mobility sector may require new governance models to achieve more consistent planning tools and challenge existing norms and structures.